Bone regeneration in critically sized rat mandible defects through the endochondral pathway using hydroxyapatite-coated 3D-printed Ti6Al4V scaffolds. Issue 55 (12th September 2018) - Wang, Yan; Cai, Xinjie; Huang, Jing; Zhou, Yi; Jiang, Tao; Wang, Yining
Abstract : Bone regeneration in critically sized rat mandible defects through the endochondral pathway using hydroxyapatite-coated scaffolds. Abstract : The endochondral approach has been proved to be a promising pathway in bone tissue engineering. However, whether it is suitable for repairing critically sized mandible defects is unknown. We designed Ti6 Al4 V scaffolds with a suitable shape and pore size by a 3D-printing selective-laser-melting technique to implement this approach. In order to improve the surface bioactivity of the scaffolds, hydroxyapatite (HA) coatings (HA/L group and HA/H group) of different crystallite size were prepared on the scaffolds via electrochemical deposition. Rat bone mesenchymal stem cells (BMSCs) were seeded onto the scaffolds and chondrogenically differentiated in vitro for 4 weeks and then the scaffolds were implanted into critically sized rat mandible defects for 8 weeks. The bare scaffold and HA coatings were characterized with field emission scanning electron microscopy, water contact angle measurements and X-ray diffractometry. Cell proliferation results showed that the bioactivity of the HA coatings could better improve the growth rate of BMSCs compared with the bare surface. Additionally, safranin O staining showed abundant cartilage matrix and chondrocytes in the HA coated scaffold. Analyses using qPCR detected higher expression of chondrogenic-related gene Col2α1 and vegfα in the HA coated groups, especially in the HA/H group. Together these data demonstrate that the HA coating could improve the chondrogenic differentiation of BMSCs. In vivo, methylene blue staining of histological sections and micro-computed tomography revealed that the HA-coated groups, especially the HA/H group, increased new bone formation via endochondral ossification compared with the control group. Therefore, this strategy provides an alternative method to improve bone formation in mandible defects via the endochondral pathway and the scaffold with larger HA crystals was superior to those with smaller HA crystals.